2009
DOI: 10.1111/j.1365-246x.2008.04017.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of dilatant and non-dilatant damage processes in oolitic iron ore:P-wave velocity and acoustic emission analyses

Abstract: S U M M A R YUniaxial and triaxial compression experiments were performed on oolitic iron ores to investigate damage processes. Most of these experiments included four indirect measurements of damage evolution, that is, P-wave velocity and maximum amplitude received during pulse transmission experiments, elastic properties (apparent Young´s modulus and apparent Poisson´s ratio) and acoustic emission (AE) monitoring. The mechanical behaviour deduced from strain measurements is dilatant for some samples and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The results reveal clearly the failure processes of rock including initiation, nucleation, and propagation of micro-fractures when the axial stress is close to the peak strength of rock. But up to now, AE technique has been less used to explore the initiation, propagation, and coalescence of brittle rock containing fissures (Jouniaux et al 2001;Wassermann et al 2009;Van De Steen et al 2005;Lei et al 2004). Van De Steen et al (2005) investigated the effect of a tensile stress gradient on fracture initiation and growth in Brazilian disk rock specimen containing a hole by AE technique, which showed that the maximum local tensile stresses the material was able to withstand increase as the stress gradient increases.…”
Section: Numerical Studies For Crack Evolution Behaviormentioning
confidence: 97%
“…The results reveal clearly the failure processes of rock including initiation, nucleation, and propagation of micro-fractures when the axial stress is close to the peak strength of rock. But up to now, AE technique has been less used to explore the initiation, propagation, and coalescence of brittle rock containing fissures (Jouniaux et al 2001;Wassermann et al 2009;Van De Steen et al 2005;Lei et al 2004). Van De Steen et al (2005) investigated the effect of a tensile stress gradient on fracture initiation and growth in Brazilian disk rock specimen containing a hole by AE technique, which showed that the maximum local tensile stresses the material was able to withstand increase as the stress gradient increases.…”
Section: Numerical Studies For Crack Evolution Behaviormentioning
confidence: 97%
“…The results reveal clearly the failure processes of rock including initiation, nucleation and propagation of micro-fractures when the axial stress is close to the peak strength of rock. But up to now, AE technique was less used to explore the initiation, propagation and coalescence of brittle rock containing fissures (Jouniaux et al 2001;Wassermann et al 2009;Van De Steen et al 2005;Lei et al 2004). Van De Steen et al (2005) investigated the effect of a tensile stress gradient on fracture initiation and growth in Brazilian disc rock sample containing a hole by AE technique, which showed that the maximum local tensile stresses the material was able to withstand increase as the stress gradient increases.…”
Section: Introductionmentioning
confidence: 97%
“…Two of these processes are particularly relevant: thermal loading and tectonic stress. Stress damage has been widely investigated during the last decades (FORTIN et al, 2007), including its time dependency (FABRE and PELLET, 2006;WASSERMANN et al, 2009). DAVID et al (1999) summarized some laboratory studies that clearly showed how thermal cracking modifies elastic moduli (BARBISH and GARDNER, 1969;HEARD and PAGE, 1982;NASSERI et al, 2007), permeability (DAROT et al, 1992;MENÉNDEZ et al, 1999), and mechanical strength (HOMAND and TROALEN, 1984;HOMAND and HOUPERT, 1989).…”
Section: Introductionmentioning
confidence: 99%